1985
DOI: 10.1111/j.1365-2923.1985.tb01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning disabilities and underachievement among university anatomy students

Abstract: In this study the relationship between underachievement in anatomy and spatial ability (both geometrical and anatomical) is investigated. Subjects were second-year medical students at the University of Cape Town from 1980 to 1983. Geometrical spatial ability was measured using a battery of three-dimensional exercises involving the sectioning, joining, translation, rotation and visualization of simple solid objects. Anatomical spatial achievement was measured using university practical examination scores of Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
5
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 13 publications
15
106
5
12
Order By: Relevance
“…Both the expert and intermediate groups outperformed the novices and this result dovetails well with other research, which suggest that inherent spatial ability becomes less important as experience takes over (Wanzel et al, 2003). It is clear from previous research that spatial ability is a reliable predictor of success in learning anatomy (Garg et al, 2001;Rochford, 1985;Guillot et al, 2006). This is all a prelude to focusing anatomy teaching on developing those spatial skills that are susceptible to change.…”
Section: Discussionsupporting
confidence: 60%
“…Both the expert and intermediate groups outperformed the novices and this result dovetails well with other research, which suggest that inherent spatial ability becomes less important as experience takes over (Wanzel et al, 2003). It is clear from previous research that spatial ability is a reliable predictor of success in learning anatomy (Garg et al, 2001;Rochford, 1985;Guillot et al, 2006). This is all a prelude to focusing anatomy teaching on developing those spatial skills that are susceptible to change.…”
Section: Discussionsupporting
confidence: 60%
“…On s'est egalement interrogĂ© sur l'Ă©volution des capacitĂ©s individuelles de RMĂ  la suite d'un entraĂźnement (Alington et al, 1992 ;Kass et al, 1998 ;Roberts & Bell, 2000 ;Hoyek et al, 2009) (Rochford, 1985 ;Garg et al, 2001 ;Hegarty et al, 2008 ;Wanzel et al, 2007 ;Guillot et al, 2007a ;Hoyek et al, 2009). Pour cela, d'autres formes de tests de RM ontĂ©tĂ© utilisĂ©es, impliquant des lettres et des chiffres (Vingerhoets et al, 2001) et mĂȘme des segments corporels (Parsons, 1994).…”
Section: Introductionunclassified
“…Recently, it has been demonstrated that visual-spatial ability (VZ) of students greatly affects their performance in a gross anatomy course, with students scoring high on the Mental Rotation test performing better on spatially complex anatomy questions [45]. Since students have different VZ, we, as educators, have the responsibility to consider this variability and appropriately implement pedagogical techniques that facilitate the acquisition of these skills [46][47][48]. It has even been suggested that anatomy teaching should focus on developing those spatial skills that are susceptible to change with experience [49,50].…”
Section: Issn: 2575-7563mentioning
confidence: 99%